Use The Positive Selection Algorithm and The Negative Selection Algorithm in The English Character Recognition - Maha Hassan; Noura Fattah; Maha Najam; Nour Shiban (College of Education for Pure Sciences, 2019)
In this paper, I use some artificial intelligence techniques algorithms, which are the algorithms of the artificial immune system (positive selection algorithm and negative selection algorithm). Through these two algorithms, it is distinguished between the original and distorted English letters.        Through the results of the patterns, which were obtained after the implementation of these two algorithms, I observed that the percentage of discrimination was 85% for the positive selection algorithm, and 80% for the negative selection algorithm.  This discrimination was applied after the images had been divided into blocks, and then the properties of the images had been extracted by adopting the method of seven undependable momentums in order to gain patterns which are close to the original pattern of the introduced English letter.